2014
DOI: 10.1080/11263504.2014.987848
|View full text |Cite
|
Sign up to set email alerts
|

Why are many anthropogenic agroecosystems particularly species-rich?

Abstract: Species-rich meadow and pasture habitats are recognised by the European Union Habitats Directive as targets for biodiversity conservation. High species richness is hypothesised to be associated with diversity in plant functional traits and life-history strategies, which are potentially restricted in situations of extremely high and low biomass production. However, variability in functional traits has yet to be investigated across a broad biomass range in nature. We measured variability in a range of functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…Indeed, Cerabolini et al . () found that many herbaceous communities in northern Italy characterised by extremely low B were dominated by R‐selected species. However, relatively few data were available for low‐B compared to high‐B systems for the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Cerabolini et al . () found that many herbaceous communities in northern Italy characterised by extremely low B were dominated by R‐selected species. However, relatively few data were available for low‐B compared to high‐B systems for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Ruderal strategists may thus contribute to both the lower asymptote and the central region of an NPP scaling curve, a phenomenon already observed for herbaceous communities in Europe (Cerabolini et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The community‐weighted mean (CWM) CSR value for each habitat type was also calculated based on species relative abundance data, following Cerabolini et al. (). For plants, the Nemenyi post hoc test was used to investigate differential abundance in the different levels of grazing.…”
Section: Methodsmentioning
confidence: 99%
“…; Cerabolini et al . ). However, each CSR analysis method has drawbacks, and all have been calibrated using local floras.…”
Section: Introductionmentioning
confidence: 97%